The impact of government policy on female HPV vaccination rates: A global perspective - Kujawa, Aleksandra; Krzeszowska , Paulina; Zajączkowska, Adrianna; Zajączkowski, Jakub; Stępniak, Kacper; Krochmal, Karolina; Pisarek, Wojciech; Wilk, Jan; Kuźma, Radosław; Marrodán-Wojtczak , Karolina (Quality in Sport, 2025)
Introduction: Human papillomavirus (HPV) is a major cause of cervical and other cancers. Vaccination is key to primary prevention, but uptake varies globally. Purpose:To analyse the impact of government policy on HPV vaccination rates among women worldwide. Material and methods: A literature review was conducted (2000–2025) using PubMed, Scopus, and Google Scholar. Inclusion criteria covered peer-reviewed articles, systematic reviews, modelling studies, and policy analyses. Brief description of the state of knowledge: Despite broad access to vaccines, global disparities persist. EU countries publicly fund vaccination, but only some meet WHO targets. Australia achieves high coverage via a school-based model. U.S. state policies significantly affect uptake. In Africa, Asia, and Latin America, barriers include access, trust, and cultural factors. Policy design and implementation strongly influence outcomes. Conclusion: Effective HPV prevention depends on coordinated national policies, public education, and accessible vaccination programmes.